Kinematic comparison of circles in cross support and circles in side support - Fujihara, T.; Gervais, P. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
"Circles" is one of the most basic skills on pommel horse. Circles can be divided into two types in terms of their supporting orientation with respect to the horse: Circles in side support—when gymnasts face perpendicular to the long axis of the horse (Side-Circles) and Circles in cross support—when gymnasts face parallel to the long axis of the horse (Cross-Circles). Although both types of Circles are equally essential for pommel horse performance, most attention has been devoted exclusively to Side-Circles. Clarifying the difference between these two types of Circles will be important for better comprehension of the skill. The purpose of this study is to investigate the kinematic difference between Side-Circles and Cross- Circles on pommel horse.